Risk Factors and Outcomes of Treatment Delays in Lyme Disease: A Population-Based Retrospective Cohort Study - Hirsch, Annemarie G.; Poulsen, Melissa N.; Nordberg, Cara; Moon, Katherine A.; Rebman, Alison W.; Aucott, John N.; Heaney, Christopher D.; Schwartz, Brian S. (Frontiers in Medicine, 2020)
Longer time between symptom onset and treatment of Lyme disease has been associated with poor outcomes. Reducing time-to-treatment requires knowledge of risks for treatment delays. We conducted a population-based study to evaluate factors associated with delayed treatment of Lyme disease and the relation between delayed treatment and post-treatment Lyme disease syndrome (PTLDS). We mailed questionnaires to 5314 individuals with a Lyme disease diagnosis or blood test followed by an antibiotic order in the medical record of a Pennsylvania health system from 2015-2017. Analyses were confined to 778 respondents who reported that they were treated for Lyme disease within the past 5 years and reported a rash and/or a positive blood test for Lyme disease. Time-to-treatment was calculated as the sum of two windows before and after seeking care for Lyme disease symptoms: time to first medical contact and time under care. We used logistic regression to evaluate factors associated with delayed time-to-treatment in each time window (> 14 days versus  14 days) and the association between total time-to-treatment (> 30 days versus  30 days) and PTLDS. We used inverse probability weighting to calculate estimates for the study’s source population (5314 individuals sent questionnaires). In the source population, 25% had time to first contact > 14 days; 21% had time under care > 14 days, and 31% had a total time-to-treatment > 30 days. Being uninsured and attributing initial symptoms to something other than Lyme disease were positively associated with delayed time to first medical contact, while seeking care at an urgent care or emergency setting (versus primary care) was negatively associated. Diagnoses between November and April and the absence of rash were positively associated with delays. Individuals whose treatment was delayed, defined as time-to treatment > 30 days had 2.26 (95% confidence interval: 1.25, 4.05) times the odds of PTLDS as those who were treated within 30 days of symptom onset. In a population-based study in Pennsylvania, one-third of Lyme disease patients reported delayed treatment, which was associated with PTLDS. To improve Lyme disease outcomes, prevention efforts should aim to reduce the time before and after seeking care.